Historical Dictionary of American Theater: Beginnings - Fisher, James (Rowman & Littlefield Publishers, 2015)
Historical Dictionary of American Theater: Beginnings covers the history of theater as well as the literature of America from 1538 to 1880. The years covered by this volume features the rise of the popular stage in American during the colonial era and the first century of the United States of America, with an emphasis on its practitioners, including such figures as Lewis Hallam, David Douglass, Mercy Otis Warren, Edwin Forrest, Charlotte Cushman, Joseph Jefferson, Ida Aldridge, Dion Boucicault, Edwin Booth, and many others. The Historical Dictionary of American Theater: Beginnings covers the history of early American Theatre through a chronology, an introductory essay, and an extensive bibliography. The dictionary section has over 1000 cross-referenced entries on actors and actresses, directors, playwrights, producers, genres, notable plays and theatres. This book is an excellent access point for students, researchers, and anyone wanting to know more about the early American Theater.